Exploring Student Perceptions of AI-Based Recruitment: A Qualitative Study at Universitas Pendidikan Indonesia - Sadullayeva, Zebo; Ciptagustia, Annisa; Rofaida, Rofi (The Eastasouth Management and Business, 2025)
This study explores the perceptions of Universitas Pendidikan Indonesia (UPI) students regarding the role of Artificial Intelligence (AI) in the recruitment process. As AI technologies increasingly influence hiring decisions through tools such as resume screening algorithms, chatbots, and video assessments, understanding how students perceive and interact with these systems is vital. Using a qualitative approach, semi-structured interviews were conducted with ten final-year and postgraduate students from various faculties. Thematic analysis revealed five major themes: limited awareness of AI tools, perceived efficiency and objectivity, concerns about bias and data privacy, a preference for human judgment, and a strong call for institutional support. While students recognized AI's potential to improve hiring outcomes, many raised concerns about bias, accountability, and lack of knowledge. The findings underscore the importance of integrating AI literacy into higher education career services to equip students with a critical understanding of AI’s role in modern recruitment. This study contributes to the discourse on digital transformation in HR by amplifying the perspectives of future job seekers in an emerging market context.